The association between performance and mathematical subjects among diploma students / Ilya Zulaikha Zulkifli ... [et al.] - Zulkifli, Ilya Zulaikha Zulkifli; Mohamad Razi, Nor Faezah; Mohammad, Nor Hazlina; Sarkam, Nor Aslily (UiTM Cawangan Perlis, 2024)
Over recent semesters, the increasing failure rates in STA108 have raised concerns about this course's teaching and learning environment. This issue has prompted an investigation into potential contributing factors, focusing on three main objectives: examining the students’ association between gender and MAT133, exploring the relationship between students’ achievements in MAT133 and their Mathematics grades in the Sijil Pelajaran Malaysia (SPM), and assessing the association between STA108 results and their Mathematics grades in the Sijil Pelajaran Malaysia (SPM). The respondents completed 329 online surveys using the purposive sampling approach. The questionnaire with two distinct parts which included the socio-demographic and other pertinent information required for analysing the respondents' profiles. The second component was the primary focus of the study. Chi-Square test was conducted to analyse the data. The test revealed no significant association between gender and MAT133. It also indicates a significant correlation between students' achievements in MAT133 and their SPM Mathematics grades. There is a significant association between STA108and their SPM Mathematics grades. Our research significantly contributes to the ongoing discussion regarding the relationship between secondary and tertiary mathematics education. It also sets the stage for further research into specific pedagogical approaches that could enhance the effectiveness of mathematics education at the tertiary level.